Translating Inhibitory Fc Receptor Biology into Novel Therapeutic Approaches. - Nimmerjahn, Falk (Journal of clinical immunology, 2016)
Innate and adaptive immune responses represent well balanced reactions aimed at resolving microbial infections without causing major collateral damage to the host. Disturbances in this system either due to enhanced activating or decreased inhibitory signaling pathways may lead to excessive immune activation resulting in tissue damage, the induction of autoimmune disease and/or chronic inflammation. On the molecular level this balance is achieved by the integration of inhibitory and activating signals, which are delivered by pairs of activating and inhibitory cell surface receptors expressed on innate and adaptive immune cells. The regulation of immunoglobulin G activity through cellular Fc receptors is a prime example for this type of regulation. This is not only relevant for the regulation of antibody-mediated effector functions through innate immune effector cells but also for the regulation of B cell activation and antibody production itself.